Application of Recommendations for Selection of Outstanding Students at Seluma 06 State Senior High School Through the Fuzzy Tsukamoto Approach - Suartana, Gede; Mesterjon, Mesterjon; Elfianty, Lena (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
SMA Negeri 6 Seluma is one of the state senior high schools in Seluma Regency. At the school, students are assessed every academic year through several criteria to select outstanding students who have the ability to master subjects and have good personal ethics. So far, the process of selecting outstanding students is only seen from the results of the report cards obtained by students, then ranking is carried out. This is of course less effective in determining outstanding students, because it must be supported by other aspects such as student ethics during the teaching and learning process. The recommendation application for selecting outstanding students at SMA Negeri 06 Seluma was made using the Visual Basic .Net programming language and SQL Server 2008r2 Database. This application has implemented one of the fuzzy logic methods, namely Fuzzy Tsukamoto which is used to help provide recommendations for selecting outstanding students at SMA Negeri 06 Seluma. The process of selecting outstanding students is carried out every academic year based on aspects based on aspects of average knowledge value, average skills score, absenteeism score, academic achievement, non-academic achievement, and guidance and counseling records. Based on the blackbox testing that has been done, the results show that the functionality of the recommendation application for selecting outstanding students at SMA Negeri 06 Seluma runs well as expected and is able to analyze student assessment data through the Fuzzy Tsukamoto Method to get recommendations for outstanding students